2003
DOI: 10.1046/j.1365-2214.2003.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Detecting emotional and behavioural problems in paediatric clinics

Abstract: There is an increased prevalence of emotional and behavioural disturbance in children attending paediatric out-patient clinics. The SDQ could be added to routine paediatric assessments to aid appropriate referral of children with a possible psychiatric disorder to child mental health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
111
0
13

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 29 publications
(40 reference statements)
12
111
0
13
Order By: Relevance
“…The Norwegian study of adolescents with epilepsy [4] as a subsample in a large epidemiological study [22] found higher self-reported SDQ scores than in adolescents without epilepsy. As rated by parents, peer problems were prevalent in our sample and were in the abnormal range for 65.6% of girls and 62.5% of boys, compared with 10.1% and 13.4% of girls and boys in the British community sample [23], and 18.0% and 21.2% in a pediatric outpatient sample [26], respectively. The study by Davies et al [3] of a British representative sample with epilepsy compared the subgroup with 'uncomplicated' epilepsy (42 out of 67 patients) to those with 'complicated' epilepsy (25 out of 67).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The Norwegian study of adolescents with epilepsy [4] as a subsample in a large epidemiological study [22] found higher self-reported SDQ scores than in adolescents without epilepsy. As rated by parents, peer problems were prevalent in our sample and were in the abnormal range for 65.6% of girls and 62.5% of boys, compared with 10.1% and 13.4% of girls and boys in the British community sample [23], and 18.0% and 21.2% in a pediatric outpatient sample [26], respectively. The study by Davies et al [3] of a British representative sample with epilepsy compared the subgroup with 'uncomplicated' epilepsy (42 out of 67 patients) to those with 'complicated' epilepsy (25 out of 67).…”
Section: Discussionmentioning
confidence: 96%
“…Norwegian normative data for parent SDQ for this age group have not yet been published. As extensive research has been performed in Great Britain based on the SDQs, we have compared our results with results from the 1999 British Child and Adolescent Mental Health survey [18,19,23], as well as to an epilepsy subsample from that survey [3], and a UK pediatric outpatient sample [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are increasingly aware that emotional and behavioural problems occur in children with chronic illness and up to 20 % of children attending a variety of paediatric outpatient clinics had a probable psychiatric disorder [21,22]. Thirty per cent of 44 patients aged 9-18 years with CKD met the criteria for depression, which was more frequent in those with longstanding disease [23].…”
Section: Introductionmentioning
confidence: 99%